Implementasi Kurikulum PAUD dalam Mendukung Transisi PAUD-SD - Yuliantina, Irma (Efektor, 2024)
The transition of the learning process from Early Childhood Education to Primary School is a crucial period for young children. During this time, children need to be well-prepared, making it essential to have a smooth educational transition to ensure their optimal growth and development. This study aims to analyze the appropriate implementation of the ECE curriculum in supporting the PAUD-SD School transition. A qualitative method is used in this research to identify the key factors that need to be considered when implementing the ECE curriculum to support this transition. The respondents of this study include school principals and ECE teachers, with data collected through in-depth interviews to illustrate how the curriculum is implemented and the foundational skills children need to be ready for Primary School. The study's findings reveal that the curriculum's goals and content are not yet contextually aligned. Teaching methods are predominantly classical, following teacher instructions, and some lessons are still delivered using drill methods. Teachers have not utilized evaluation processes to enhance learning quality, and initial assessments are not conducted as a basis for planning instruction. Understanding the transition of PAUD SD in implementing the PAUD curriculum provides changes in the way teachers carry out the child-centered learning process.